Cerebrovascular reactivity metrics as predictors of cognitive performance in healthy ageing: insights from transcranial colour‑coded ultrasound - Ackah, Joseph Amihere; Chen, Xiangyan; Zeng, Huixing; Zhong, Jingxin; Chan, Jason Tsz Lok; Lo, Michael Lung Cheung; Cai, Jing (The Ultrasound Journal, 2025)
Introduction: This study was designed to investigate the utility of cerebrovascular reactivity (CVR) metrics, derived from transcranial colour-coded Doppler ultrasound (TCCD). Three main CVR metrics were examined as potential markers for cerebrovascular risk associated with mild cognitive impairment (MCI), a stage between normal cognition and dementia.Methods: We investigated 122 eligible, stroke-free, healthy, community-based Chinese adults (mean age, 65.34 ± 6.86 years). Cognitive performance was assessed using the validated Hong Kong version of the Montreal Cognitive Assessment. On a scale of 0–30, participants with low scores